Defining a spectrum of integrative trait‐based vegetation canopy structural types. (16th September 2019) - Fahey, Robert T.; Atkins, Jeff W.; Gough, Christopher M.; Hardiman, Brady S.; Nave, Lucas E.; Tallant, Jason M.; Nadehoffer, Knute J.; Vogel, Christoph; Scheuermann, Cynthia M.; Stuart‐Haëntjens, Ellen; Haber, Lisa T.; Fotis, Alexander T.; et al.
Abstract: Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning. We use the multivariate structural trait composition of vegetation canopies to classify ecosystems within a global canopy structure spectrum. Across the temperate forest sub‐set of this spectrum, we assess gradients in canopy structural traits, characterise canopy structural types (CST) and evaluate drivers and functional consequences of canopy structural variation. We derive CSTs from multivariate canopy structure data, illustrating variation along three primary structural axes and resolution into six largely distinct and functionally relevant CSTs. Our results illustrate that within‐ecosystem successional processes and disturbance legacies can produce variation in canopy structure similar to that associated with sub‐continental variation in forest types and eco‐climatic zones. The potential to classify ecosystems into CSTs based on suites of structural traits represents an important advance in understanding and modelling structure–function relationships in vegetated ecosystems. Abstract : Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning and can be defined by a global canopy structure spectrum. We utilized the multivariate structural trait composition of vegetation canopies to classify temperate forest ecosystems across a subcontinental scale data set, and illustrated variation along three primary structural axes and resolution into six largely distinct and functionally relevant canopy structural types. The potential to classify ecosystems into canopy structural types based on suites of structural traits represents an important advance in understanding and modeling structure‐function relationships in vegetated ecosystems.